Advancing river flow monitoring with small uncrewed aircraft and simulation-driven development - Dille, Michael; Vespignani, Massimo; Bruce, Jonathan; Wong, Uland (Frontiers in Remote Sensing, 2025)
Current streamgaging processes for river flow rate estimation are typically slow and often hazardous, leading to inadequate coverage across national waterways. This paper presents a semi-autonomous aerial monitoring system that is designed for rapid river flow gaging, building upon a recently developed sensor package that is mounted beneath a small uncrewed aerial vehicle. This package consists of, among other instruments, a mid-wave infrared camera that can be used to detect minute thermal variations in the water surface, from which a particle image velocimetry algorithm is used to extract flow estimation. The design and testing of this sensor package and velocimetry algorithm for field evaluation are discussed, and a simulation environment facilitating the development of algorithms for automatic a priori and live-adaptive vehicle trajectory planning is presented. The simulation environment captures a physically based approximation of vehicle flight characteristics, contains digital terrain models of field test sites, and incorporates water surface flow maps generated from numerical flow simulation data and real-world measurements. Field and simulation results are presented validating the design of the sensor package and the use of simulation as a digital twin for aerial streamgaging development. This framework and the lessons learned to date lay the foundation for accelerated improvements in waterway measurement for both routine and disaster response purposes requiring rapid deployment in novel locations.